2020
DOI: 10.1016/j.lfs.2020.117329
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-mediated regulation of Nrf2 signaling pathway: Implications in disease therapy and protection against oxidative stress

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 141 publications
1
33
0
Order By: Relevance
“…Under physiological conditions, the NRF2 expression level is low; however, it can be induced significantly under the influence of factors causing oxidative stress, such as poisoning, volatility, hyperglycemia, and hypoxia [53,54]. Our observations are consistent with the classical pattern of NRF2 activation [50]. In addition, the level of NRF2 in the cytoplasm was significantly downregulated after OTA treatment, and the level of NRF2 in the cytoplasm was even lower after ASX pretreatment.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Under physiological conditions, the NRF2 expression level is low; however, it can be induced significantly under the influence of factors causing oxidative stress, such as poisoning, volatility, hyperglycemia, and hypoxia [53,54]. Our observations are consistent with the classical pattern of NRF2 activation [50]. In addition, the level of NRF2 in the cytoplasm was significantly downregulated after OTA treatment, and the level of NRF2 in the cytoplasm was even lower after ASX pretreatment.…”
Section: Discussionsupporting
confidence: 87%
“…NRF2 is an important transcriptional activator of antioxidant genes and is important in antioxidant protection [49]. After activation of the NRF2 signaling pathway, it contributes to the expression of a series of downstream antioxidant proteins, such as NQO1, HO-1, γ-GCS, and GSH-Px [50]. Previous studies have also shown that grape seed proanthocyanidins reduce the cytotoxicity of cisplatin-induced human embryonic kidney cells by regulating NRF2/HO-1 in vitro [51].…”
Section: Discussionmentioning
confidence: 99%
“…miRs, such as miR-144, miR-28, and miR-93, diminish the Nrf2 signaling pathway via various mechanisms [ 149 , 150 , 151 ], whereas miR-200a and miR-7 activate Nrf2 signaling pathway by targeting keap1 [ 151 , 152 ]. There is a comprehensive review on miR-mediated regulation of Nrf2 activity [ 153 ].…”
Section: Discussionmentioning
confidence: 99%
“…The contribution of miRNAs to the regulation of NRF2 signaling is widely recognized. For example, downregulation by targeting the 3 untranslated region (3 UTR) "seed" sequences in NFE2L2 mRNA has been reported for miR-153, miR142-5p, mi-R27a, miR-144, miR34a, and miR-93 (reviewed in [48,49]). On the other hand, an increase in NRF2 expression and activity was observed by miRNAs targeting the 3 UTR of KEAP1 mRNA.…”
Section: Regulation By Non-coding Rnasmentioning
confidence: 99%